Improving the competence of teacher candidates in Islamic religious education through project-based learning with outcome-based curriculum - Alhamuddin, Alhamuddin; Wasehudin, Wasehudin; Dermawan, Oki; Murniati, Andi (Journal of Islamic Education and Innovation, 2024)
This study explores the implementation of project-based learning as a strategy to facilitate the development of competencies among prospective Islamic Religious Education teachers candidates within the framework of an outcome-based curriculum. This qualitative research employed a descriptive method and was conducted at the Islamic Education Study Program, Faculty of Tarbiyah and Teacher Training, Universitas Islam Bandung. Data collection techniques included observation, interviews, document analysis, and assessment of student project outputs. Thematic analysis was used to identify key patterns and themes through data reduction, categorization, and interpretation. The findings indicate that studying and internalizing learning model theories, producing teaching simulation videos, conducting teaching practice, and creating mind maps of learning activities played a significant role in shaping students’ pedagogical and analytical skills. Overall, the integration of these activities contributed to the achievement of outcome-based curriculum goals. It is recommended that future applications of this model consider cross-disciplinary student collaboration and the integration of technology to enhance innovation in learning.